Meaning of Life Siswa Sekolah Menengah Pertama dengan Latar Belakang Budaya Samin - Amalia, Maghfirotul; Hidayah, Nur; Fauzan, Lutfi (Jurnal Kajian Bimbingan dan Konseling, 2017)
This study aims to describe the junior high school students with Samin cultural background’s meaning of life of that comes from: creative values, experiential values and attitudinal values. This study follows the steps of survey types in a descriptive quantitative approach. The instruments used are developed in inventory. Data were analyzed by using descriptive analysis technique and SPSS 20.0 for Windows in order to determine the frequency, percentage, standard deviation, skewness. Results show that junior high school students with Samin cultural background was able to find the meaning of life through three sources of value, which experiential values reach the highest percentage (45%) followed by attitudinal value (29%), and the creative value (26%). In particular, these results illustrate that the fulfillment of meaning of life of junior high school students with a cultural background of Samin is in accordance with the Samin culture which prioritizes appreciation of the values of life before acting and responding to something.